Analysis of cocoa particle roasting process in a μ-reactor. (October 2022) - Rojas, Myriam; Granados, David; Osorio, Jessi; Chejne, Farid
Abstract: Thermal energy changes the chemical composition of cocoa, which is related to its quality, during roasting. The effect of the heating rate on the physicochemical changes of cocoa, and the dynamics of generation and degradation of volatile compounds during heating are still unknown. Therefore, the weight loss of cocoa and the chemical composition of the released gases released at temperatures from 40 to 350 °C were identified in using a μ-reactor (PTV-GC-MS) with heating rates of 2 (β1 ), 4 (β2 ), and 8 °C sec −1 (β3 ). The thermal process was divided into three stages (raw ‒ dry, dry – roasted, and roasted – over-roasted). Higher heating rates cause lower volatilization at the same temperature due to shorter residence times. Likewise, more compounds were identified in the gas-fraction at β1 than at β2 and β3 with the same temperatures. Also, a 2D phenomenological model coupled to kinetics was made to predict phenomena such as thermal differentials, water and gas content, solid fractions, conversion, pressure, and gas outlet rate. Highlights: Cocoa quality begins in the tree and develops in the processing. Small-scale studies and modelling are valuable tools to understand cocoa roasting. A 2D model coupled to kinetics was able to show experimentally invisible phenomena.